PENGARUH LOKASI, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA WARUNG BRADER KEDIRI - Wijayanti, Reni Fitri Dwi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to determine the effect of location, price, and service quality on customer satisfaction at Warung Brader. This study uses a quantitative approach and uses secondary and primary data. Samples were taken by 40 respondents using purposive sampling method. The data analysis technique used was descriptive statistics, classical assumption test, multiple linear regression, determinant coefficients and hypothesis testing. The results showed that location and service quality had an effect on customer satisfaction, price had no effect on customer satisfaction. The relationship between location, price, and service quality variables simultaneously affects customer satisfaction. The results of this study differ from the reference which shows that there is an effect of price on customer satisfaction. This means that the owner can provide prices according to the expectations of Warung Brader's customers.